P93 The practicalities of using allergen-impermeable bed covers in children with mite allergic asthma. (12th November 2015) - Sumner, H; Begum, H; Simpson, A; Custovic, A; Murray, CS
Abstract : Objective: As part of a randomised double-blind placebo-controlled study in children with mite-allergic asthma, mite-impermeable bedding encasings were evaluated in terms of reduction in allergen exposure and patient/parent acceptability. Methods: Physician diagnosed asthmatic children (3–17 years) were recruited following an exacerbation of asthma. Mite-sensitised children were randomised to either mite-impermeable encasings for the mattress, pillow and duvet (Astex Pristine; ACP solutions, Gloucestershire, UK) or placebo encasings (100% polycotton; Musbury fabrics, Rossendale, UK), in a double-blind manner. Vacuumed dust samples were collected from the child's mattress prior to fitting the encasings and at 12 months, stored at -20°C, then analysed for mite allergen content (Der p1) by enzyme-linked immunosorbent assay (Indoor Biotechnologies, Cardiff, UK). Questions aimed at assessing the practicalities of using the encasements were asked of parents by an interviewer blind to their allocation, 8–12 months later. Results: 284 children (mean age 7.7 years; 65.8% male) were randomised (146 active; 136 placebo). There was an 84% decrease in Der p 1 levels in child's mattress in those using the mite-impermeable encasings, which was not seen in the Placebo group (p < 0.001). Data on 'use of bedding encasements' were obtained from 232 participants. Significantly more families in the active group reported that the duvet slipped within its cover, compared to the placebo group (32.2% vs 5.3% respectively, p < 0.001) and that it was "noisy" (14.4% active vs 0.9% in placebo, p < 0.001). Some reported the extra covers made them too warm (3.4% active vs 1.8% placebo, p = 0.64). Overall 31(26.3%) using the mite-impermeable encasings rated them as "uncomfortable" compared with 2(1.8%) in the placebo group (p < 0.001). Furthermore, 30(25.4%) children in the mite-impermeable group said they would prefer to have the encasings removed, compared to 3(2.6%) in the placebo group (p < 0.001). There was no difference in the numbers of families who stated that they would continue to use the encasings if it were of benefit to the child, (87.3% mite-impermeable vs 89.35% placebo p = 0.68) Conclusions: Mite-impermeable encasings can significantly reduce mite allergen levels in the bed. Despite some practical issues, most families are willing to use this intervention if it is of benefit to their child's asthma.